Interactive Math Adventures for Primary Students (IMAPS) - Adnan, Muhammad Fikri Hakim; Vikraman, Pavan Vikram; Azreen, Muhammad Haziq Hakim; Abdul Razak @ Lapochik, Fauziah; Mohd Hanifa, Rafizah (Multidisciplinary Applied Research and Innovation, 2026)
Mathematics is one of the core subjects for primary school students but still there are many students lacks of confidence and engagement that lead to poor learning outcomes. This lead us to develop Interactive Math Adventures for Primary Students (IMAPS), an adventure-based interactive web game designed using Unity and C# to teach basic math concepts through gaming challenge concepts. IMAPS features a knight versus monster battle system in which a correct answer allows students to attack the monster while the wrong answer allows the monster to attack their character; it motivates the students to solve the problems across 30 levels. Features that are included in the game are statistics tracking,progress monitoring, and understanding of basic arithmetic operations. Evaluation results indicate that IMAPS effectively improves student engagement and understanding of basic arithmetic operations. In future, enhancement will focus on expanding the content scope and improving adaptive learning to further personalise the educational experience.